High-level biosynthesis and purification of the antimicrobial peptide Kiadin based on non-chromatographic purification and acid cleavage methods - Liangjun Zheng; Fengyi Yang; Chen Wang; Muhammad Zafir; Zishuo Gao; Pilong Liu; Fatma A. El-Gohary; Xin Zhao; Huping Xue (Biotechnology for Biofuels and Bioproducts)
Abstract Antimicrobial peptides (AMPs) are renowned for their potent bacteriostatic activity and safety, rendering them invaluable in animal husbandry, food safety, and medicine. Despite their potential, the physiological toxicity of AMPs to host cells significantly hampers their biosynthetic production. This study presents a novel approach for the biosynthesis of the antimicrobial peptide Kiadin by engineering a DAMP4–DPS–Kiadin fusion protein to mitigate host cell toxicity and achieve high-level expression. Leveraging the unique properties of the DAMP4 protein, we developed a non-chromatographic purification method to isolate the DAMP4–DPS–Kiadin fusion protein with high purity. The instability of the D–P peptide bond under acidic conditions, combined with the thermal and saline stability of DAMP4, enabled efficient separation of Kiadin through acid cleavage and isoelectric precipitation, yielding Kiadin with 96% purity and a production yield of 29.3 mg/L. Our optimization of acid cleavage temperature, duration, and isoelectric precipitation conditions proved critical for maximizing the purification efficiency and expression levels of Kiadin. The biosynthesized Kiadin exhibited robust bacteriostatic activity against Escherichia coli, Pseudomonas aeruginosa, Acinetobacter baumannii, Bacillus cereus and Staphylococcus aureus. Notably, Kiadin demonstrated significant post-antibiotic effects by disrupting bacterial membrane integrity, inducing cytoplasmic leakage, and inhibiting biofilm formation in E. coli K88 and S. aureus Mu50, without cytotoxicity towards mouse macrophages. In vivo studies further confirmed Kiadin's exceptional therapeutic efficacy against abdominal infections caused by E. coli K88. The acid cleavage and non-chromatographic purification techniques developed in this study offer a cost-effective and efficient strategy for the high-purity production of AMPs.